Structural funds and development of non-profit organisations - Marciszewska, Anna (Economics of the 21st Century, 2014)
The article contains theoretical considerations connected with the influence of structural funds on the development of non-profit organisations. Theoretically, the access to these funds should ensure development of these entities. However, as practice shows it is not always the case. We observe development dynamics of this sector and constantly unused social potential. These organisations are subject to continuous pressure directed towards full use of their resources and growth in effectiveness of activities undertaken. However, the pace of their development is mainly dependent on funds allocated for their development, therefore it seems legitimate to financially support activities of non-profit organisations from, inter alia, structural funds. These resources enable to earn experience which positively affects their development. However, the success of majority of non-profit organisations is not based on the structural funds. Managing persons are very careful during a process of acquiring, implementing and accounting for EU-supported projects. They think that this process is not always successful. The article draws attention to the fact that structural funds can be a key for development of non-profit organisations, yet provided that applying for financial support will not be accidental and will constitute an organised sequence of activities
Ekonomia XXI Wieku = Economics of the 21st Century, 2014, Nr 4 (4), s. 126-143
Keywords: non-profit organisations; structural funds; EU projects; organizacje non-profit; fundusze strukturalne; projekty unijne